2000
DOI: 10.1002/1522-2683(20000801)21:14<2969::aid-elps2969>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage promotes mistyping in the allele specific oligonucleotide probing analysis of forensic samples

Abstract: Five polymerase chain reaction (PCR) products which could not be reliably typed by allele-specific oligonucleotide (ASO) probing at the human leukocyte antigen (HLA) DQA1 locus were analyzed by polyacrylamide gel electrophoresis and direct sequencing. The first method revealed the preferential amplification of only one of the two alleles in two cases. Direct sequencing of PCR products allowed unambiguous genetic typing but a high number of artifacts was observed. Several of these artifacts occurred in the sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(23 reference statements)
2
6
0
Order By: Relevance
“…We excluded three published sequences (Gogo1*0306, Gogo5*0201, Gogo5*0401) that are probably products of in vitro recombination. This occurrence of artificial sequences while typing the MHC‐DRB has been both described and demonstrated experimentally by others (Fattorini et al . 2000; Longeri et al .…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…We excluded three published sequences (Gogo1*0306, Gogo5*0201, Gogo5*0401) that are probably products of in vitro recombination. This occurrence of artificial sequences while typing the MHC‐DRB has been both described and demonstrated experimentally by others (Fattorini et al . 2000; Longeri et al .…”
Section: Resultssupporting
confidence: 67%
“…1998). Concern regarding the low amount of template present in the PCRs led us to use 40 cycles in the amplifications of the MHC‐DRB loci, and the proportion of apparent recombinants we observed was similar to that described from the use of damaged DNA from forensic samples (Fattorini et al . 2000).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies [19,24] showed a high frequency of sequencing artefacts and unreliable genetic characterisations in aged forensic samples. Identification and quantification of human DNA in the extracts from the biological samples and the degree of chemical decay of its primary structure should be considered for a reliable evaluation of the PCR typing results.…”
Section: Discussionmentioning
confidence: 97%
“…1999), sequences that arise from nucleotide misincorporations or artefactural recombination in PCRs that start from few or single molecules can only be detected by screening more than one reaction (e.g. Fattorini et al . 2000; Nino‐Vasquez et al .…”
mentioning
confidence: 99%